Designing a Fallen Tree Disaster Reporting Application Based on Mobile Android Case Study: Regional Disaster Management Agency (BPBD) Banyumas Regency - Fera Agurini; Aulia Desy Nur Utomo; Fahrudin Mukti Wibowo (Jurnal E-Komtek, 2022)
Banyumas Regency is prone to falling trees in the rainy season, but the report on fallen tree disasters is still not focused. The large number of social media used and the regent's complaint booth confuses the reporting process because it is not centralized in one system, making data recording difficult. The authorities in handling the fallen tree disaster are the Regional Disaster Management Agency (BPBD) of Banyumas district. With these problems, an android application was designed that functions to facilitate the process of reporting disasters from the community, as well as the process of recording fallen tree disaster data. The design stage uses the Waterfall method, and the testing uses UAT and black box testing. The testing was carried out by three users, namely the Community, Admin, and Officers. The respondents from the community as many as 120 people, as many as 20 officers, and admin as many as 3 people. The results of the UAT application test are that the application is very helpful for the disaster reporting process; the menu display is attractive; the application can be understood; the type, font size, and color is easy to read; and the users do not find it difficult to make an account, and the application menu meets the users’ needs. In the black box testing, it was found that the designed application was very helpful with an average validation percentage of 98% for each menu.